Founders and the success of start-ups: An integrative review - Himawat Aryadita; Badri Munir Sukoco; Maurice Lyver (Cogent Business & Management, 2023)
This study aims to identify the factors that must be present when founders develop start-ups and why these factors affect the success of start-ups. Despite the importance of founders' involvement in start-up success, few studies have specifically and comprehensively focused on founders as the main factor in start-up success. This study presents an integrative literature review of start-up success studies published between 2010 and 2020 on the Web of Science. The study finds that the main founder-related factors that influence start-up success can be categorized as Knowledge, Experience, Competence, Characteristics, and Founding Team (KECCT). KECCT determinants have a substantial impact on strategic decision making, which ultimately determines start-up performance. The dynamic process that founders need to follow in building successful start-ups is described as the start-up success framework. The start-up success framework can be used for further research and by practitioners in developing start-ups. Our review indicates that previous studies have put more emphasis on the cognitive (rational) characteristics of the founder. Based on the Trilogy of Mind Theory, we add the emotional and motivational characteristics of the founder that contribute to the success of a start-up. Our proposed framework, the ERM Model, also enriches the upper echelons theory.
Keywords: 650; economic development; founder; innovation; integrative review; start-up